A rapid analytical method of major milk proteins by reversed‐phase high‐performance liquid chromatography. (26th May 2017) - Ma, Lu; Yang, Yongxin; Chen, Jingting; Wang, Jiaqi; Bu, Dengpan
Abstract: A reversed‐phase high‐performance liquid chromatography (RP‐HPLC) method with rapid and automated analysis, good separation, high resolution, high accuracy and reproducible results was successfully developed and used to separate and quantify the major cow milk proteins within 30 min analytical time. Standard solutions of single purified cow milk proteins were used to develop calibration equations. The RP‐HPLC method was validated with respect to intra‐day repeatability, inter‐day precision, linearity, accuracy and limit of detection (LOD). The recoveries of the RP‐HPLC analyses of major milk proteins from cows ranged 71.0–114%, the inter‐day precision was expressed as the relative standard deviation, and the ranged from 1.51 to 4.60% and the LOD ranged from 0.08 g/L to 0.28 g/L. Major proteins in cow were quantified according to the chromatographic profiles. Results showed that a rapid RP‐HPLC method for quantifying the major cow milk proteins was developed, which could be used to determine milk protein contents in the dairy industry.